Building High-Quality Online and Blended Learning: An Evidence-Informed Framework Integrating Community of Inquiry, Teaching Presence, and Learner Support - Carlos Emilio Fuentes Carlos Emilio Fuentes (Educational Innovation and Learning Transformation, 2025)
Online and blended learning have become central modalities in contemporary education across schooling, higher education, and professional development contexts, yet quality remains deeply uneven when instructional designs prioritize content delivery over the conditions that genuine learning requires. Evidence accumulated across decades of distance education research and learning sciences scholarship consistently highlights the primacy of interaction quality, instructor facilitation, and learner support structures as the determinative factors in online learning outcomes, a finding that the rapid, crisis-driven expansion of online provision in recent years has made more urgent to translate into institutional practice. This evidence-informed conceptual paper synthesizes foundational research on transactional distance, the Community of Inquiry framework encompassing teaching presence, social presence, and cognitive presence, and the instructional design evidence base on feedback, retrieval practice, and persistence support, to propose a practical framework for high-quality online learning conditions. The framework articulates four interdependent domains: (a) teaching presence as purposeful design and facilitation infrastructure; (b) cognitive presence supported through structured inquiry cycles and feedback-to-revision loops; (c) social presence and belonging through equity-conscious participation design; and (d) learner support and equity-by-design, including accessibility provisions, workload-sensitive pacing, and ethical use of learning analytics. Three conceptual tables operationalize the framework by providing a Community of Inquiry-to-design mapping of concrete course routines, a persistence and wellbeing support matrix calibrated to identifiable risk patterns, and a quality assurance checklist for programs and institutions. The paper concludes with recommendations for educators, instructional designers, and institutional leaders aiming to scale online learning responsibly without relying on weak engagement proxies or treating technology adoption as a substitute for pedagogical design.